2016
DOI: 10.1111/opn.12117
|View full text |Cite
|
Sign up to set email alerts
|

Carer engagement in the hospital care of older people: an integrative literature review

Abstract: The integrated model of carer engagement developed here could help staff and hospitals to develop strategies, staff training and resources that work with rather than against carers. The findings can inform future research on carer engagement interventions and associated outcomes for patients, carers and staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 111 publications
1
27
0
1
Order By: Relevance
“…Caregivers also assessed readmission more preventable when patients did not feel ready for discharge. Literature shows that caregiver engagement can improve continuity of care by providing a consistent relationship for patients during their journey through the multiple and complex transitions in care 39. Caregivers play an important role in the transfer and additional care at home, which could potentially prevent readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers also assessed readmission more preventable when patients did not feel ready for discharge. Literature shows that caregiver engagement can improve continuity of care by providing a consistent relationship for patients during their journey through the multiple and complex transitions in care 39. Caregivers play an important role in the transfer and additional care at home, which could potentially prevent readmission.…”
Section: Discussionmentioning
confidence: 99%
“…The search outputs were then scanned across title, author and abstracts to determine suitability to inform the review. From this, full papers deemed relevant to (i) the keywords focus and (ii) informative for those new to the points under discussion were also scrutinised for their references, adding to the papers for final inclusion (akin to purposive sampling) (Morrow & Nicholson, ). In addition, the literature reviewed relied on mining articles’ reference lists (i.e., snowball sampling) for relevant publications (Morrow & Nicholson, ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a more recent study in the United Kingdom showed that family caregivers of hospitalised older people felt relegated to 'outsider' status, excluded and unrecognised for their caregiving role and expertise, and experienced frustration and anger (Lowson et al, 2013). From a more practical perspective, an integrative review (Morrow and Nicholson, 2016) and a recent Australian study (Slatyer et al, 2013) have both drawn attention to FECH and caregiver impacts 2 the limited opportunity for the hospital staff to liaise with family caregivers regarding discharge in the scarce time available.…”
Section: Caregivers Of Older People In Hospitalmentioning
confidence: 99%